Bioethics and the posthumanities - Sands, Danielle (London: Routledge, 2022)
c
Introduction: Encounters between bioethics and the posthumanities / Danielle Sands -- Therapy, enhancement, and the social model of disability / Michael Wee -- Rethinking the posthuman in bioethics / David Boden and Sarah Chan -- Gen-ethics, policy and the posthumanities / Ruth Chadwick -- Questioning the politics of human augmentation technologies / Anna Roessing and Tom Hobson -- Biohumanities / Stefan Herbrechter -- Autonomous : bioethics and/as intellectual property / Megen de Bruin-Molé -- A posthumanist critique of de-extinction science / Sarah Bezan -- You can't take responsibility for yourself : humans as networks and posthumanistic culpability / Matt Hayler -- The filter problem for posthuman bioethics / David Roden.
Keywords: Bioethics -- Philosophy; Posthumanism; LITERARY CRITICISM / General